2022
DOI: 10.1002/mame.202100822
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress on Multilayer‐Structured Polymer‐Based Dielectric Nanocomposites for Energy Storage

Abstract: The demand for a new generation of high‐energy‐density dielectric materials in the field of capacitive energy storage is promoted by the rise of high‐power applications in electronic devices and electrical systems. Polymer‐based dielectric nanocomposites with ultrahigh charge–discharge rates and power densities play essential roles in energy storage. Recently, multilayer structure polymer‐based dielectric nanocomposites (MSPBDNs) with improved dielectric constant, breakdown constant, and discharged energy dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 73 publications
(112 reference statements)
0
11
0
Order By: Relevance
“…Generally, the approximation accuracy of Shape Function Interpolation increases with the order, so the number of unit control points and Gaussian Quadrature points also increase. The FEM can solve for the electric field distribution of the polymer dielectric to guide the microstructure, [93] for example, by setting the upper electrode to potential and the under electrode to ground, while imposing a second type of Neumann boundary condition on the transverse structure, written as:…”
Section: Finite Element Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the approximation accuracy of Shape Function Interpolation increases with the order, so the number of unit control points and Gaussian Quadrature points also increase. The FEM can solve for the electric field distribution of the polymer dielectric to guide the microstructure, [93] for example, by setting the upper electrode to potential and the under electrode to ground, while imposing a second type of Neumann boundary condition on the transverse structure, written as:…”
Section: Finite Element Modelmentioning
confidence: 99%
“…Generally, the approximation accuracy of Shape Function Interpolation increases with the order, so the number of unit control points and Gaussian Quadrature points also increase. The FEM can solve for the electric field distribution of the polymer dielectric to guide the microstructure, [ 93 ] for example, by setting the upper electrode to potential and the under electrode to ground, while imposing a second type of Neumann boundary condition on the transverse structure, written as: ϕtruen^badbreak=0\[ \begin{array}{*{20}{c}}{\frac{{\partial \phi }}{{\partial \widehat n}} = 0}\end{array} \] where n is the unit outer normal vector and φ is the potential waiting to be solved. If the solution region satisfies the electrostatic field condition, then φ satisfies the Laplace equation: Δ2ϕbadbreak=0\[ \begin{array}{*{20}{c}}{{\Delta ^2}\phi = 0}\end{array} \] …”
Section: Typical Classifications Of Modelingmentioning
confidence: 99%
“…S1 (ESI†), thus the U d of a nonlinear polymer dielectric can be measured as: , and the efficiency is: η = U d /( U d + U l ), where D is electrical displacement and U l is energy loss. 7 According to the above formula, the U d of polymer dielectric materials is closely related to the ε r and E . Based on the above reasons, enhancing the properties of polymer-based nanocomposites through adding nanofillers with high permittivity has been extensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…11 In a multilayer configuration, the interfaces of each layer can boost Maxwell-Wagner interfacial polarization and impede the electrical breakdown path simultaneously, resulting in improvement of the dielectric constant, breakdown strength, and energy storage ability as well. 12 According to this theory, we designed a bilayer structured PET-acrylic resin/BaTiO 3 (BT) composite film whose dielectric constant increased by about 26% at 60 vol% BT loading compared with the pristine PET film. 13 Wang et al 14 reported sandwich-structured dielectric nanocomposites whose middle ''hard layer'' with 1 vol% BT@PVDF improved the breakdown strength and two outer ''soft layers'' with 10-50 vol% BT@PVDF provided a high dielectric constant.…”
Section: Introductionmentioning
confidence: 99%